(untitled) (Economics and region, 2021)
The article defines that sales – a system of relations in the field of commodity-money exchange between economic and legal entities of the market, commercial needs that meet their own. The subjects of the market are sellers and buyers, and the object of sale is the product itself. The sales activity of the enterprise is based on the results of marketing analysis of the market. The main objectives of this analysis are to find ways to most fully meet consumer demand, increase sales, make the most use of enterprise resources, reduce commercial risks. It is noted that sales problems of enterprises need to be addressed during the development of marketing policy. The development of sales policy of the enterprise should be based on the results of the analysis of the existing sales system. Moreover, this analysis should be carried out not only in quantitative terms, but also in qualitative: the level of service, customer satisfaction and commitment, the effectiveness of communication policy, the correct choice of market segments, the effectiveness of sales staff and more. To substantiate the sales policy, it is necessary to choose the optimal option for calculating costs in terms of the main areas of implementation of the sales policy of the enterprise. Active forms of sales are distinguished: trade by preliminary orders; TV sales, sales via the Internet; direct mail; personal sale. The planning of sales activities of the enterprise is determined by the financial estimate of sales, in which the main place is occupied by the costs of circulation. They can be calculated based on forecasts of sales and trading costs. As a result of summarizing individual estimates for each product group is a consolidated sales estimate. General trade costs include: wages of sales staff, transportation and warehousing costs, trade discounts, etc. Responsibility for budgeting and monitoring compliance is entrusted to the management of the sales department. An important point in planning is to set sales targets for a certain period of time, their definition can not be reduced to a mechanical division of sales by the number of commissioners who are responsible for sales or a particular group of goods or in a particular geographical area or market sector. The scope of work of these commissioners is influenced by many different factors: geographical factors, product (one type, group, the whole range), nature of activities (visiting new customers, repeat orders, specialized work), unit of measurement, base of measurement, time period, reward base.